Warna dan Kata: Pelatihan Penciptaan Produk Literasi Visual oleh Anak dan Orang Tua di TBM Ransel Buku, Kelurahan Petuk Katimpun, Kalimantan Tengah Tahun 2025: Color and Word: Training on Creating Visual Literacy Products by Children and Parents at TBM Ransel Buku, Petuk Katimpun Village, Central Kalimantan 2025 - Christy, Nirena Ade; Veniaty, Syarah; Ramadhan, Ibnu Yustiya; Pratiwi, Endah Yusma; Jeje, Jeje; Waruwu, Sedih Hati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Parental participation in children’s literacy activities at TBM Ransel Buku in Petuk Katimpun Village has not been optimal. Additionally, there is limited availability of visually engaging learning media, and no mechanism for publishing collaborative products between children and parents. This community service aims to address those problems by enhancing active parental participation, developing children’s visual expression and parents’ narrative skills, and creating tangible collaborative visual literacy products. The program was implemented over 6 months using participatory training and experiential learning methods. Activities included socializing, visual literacy concepts, drawing training for children (21 participants), creative narrative writing training for parents (19 participants), collaborative creation, mentoring, editing, and the production and publication of an anthology. As a result, parental participation increased to 95%, 90% of children showed improved visual expression, and 90% of parents demonstrated enhanced narrative skills. The main outputs produced were a collaborative QRCBN-registered anthology book titled "Gambarku, Ceritamu, Cerita Kita," a documentation video, three online media publications, and a training module. The collaborative visual literacy approach proved effective in improving individual skills and strengthening family emotional bonds, as well as the institutional capacity of TBM.